Estructuración y operacionalización del proyecto de expansión para la empresa "Sunflower" - Guevara Alvarado, Valeria Catalina (2015)
Companies in the textile apparel sector of the country experiencing a harsh reality within production costs, due to the excessive entry of Chinese products, SUNFLOWER is an SME that has unfolded over five years in the market Ipiales Quito, maintaining an angry competition with smuggled goods sold in the informal market of that sector.